ANALYSIS AND OPTIMIZATION OF CRACKING IN THE CATALYST OF AN EXTENDED-RANGE THREE CYLINDER ENGINE - HONG Yang; XIE ZuTong; REN JianPing; YE NengYong (Jixie qiangdu)
Aiming at the cracking problem of the catalyst of an extended-range three cylinder engine in the durability test, the fracture form and the cracking reason were analyzed, the optimization and verification were carried out. The fracture and material were analyzed by means of chemical composition detection, metallographic structure analysis and fracture electron microscope scanning. The vibration characteristics of the three cylinder engine were discussed, and the heat transfer analysis and thermal modal analysis of the catalyst were carried out. The cracking reason was determined by modal interferogram and strain energy density. An improved scheme was proposed based on the modal frequency and mode shape, and the analysis and verification were taken. The results show that the surface of the engine catalyst will form intergranular cracks under high temperature oxidation. When the stiffness of the support is insufficient, the thermal modal frequency of the catalyst is too low, it will resonate with the third-order combustion excitation of the three cylinder engine under high temperature, leading to the propagation of surface cracks and the formation of fracture. By analyzing the thermal modal frequency, vibration mode and strain energy density of the catalyst, the catalyst support can be effectively improved, which provides a reference for the design of the catalyst of the three cylinder engine.